2000
DOI: 10.1080/02724980050156290
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clause wrap-up on eye movements during reading

Abstract: The effect of clause wrap-up on eye movements in reading was examined. Readers read passages in which a target category noun referred to either a high typical or a low typical antecedent. In addition, the category noun was either clause final or non-clause final. There were four primary results: (1) Readers looked longer at a category noun when its antecedent was a low typical member of the category than when it was a high typical member; (2) readers looked longer at the category noun and at the post-category … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 0 publications
9
129
1
1
Order By: Relevance
“…However, readers made regressive eye movements from this region more frequently when it ended with a comma (12.2% vs. 7.3%; 95% confidence interval of the difference from 1.1% to 8.7%). As noted above, this is consistent with previous findings of increased regressions before a clause-final comma (Hirotani et al, 2006;Rayner et al, 2000). There was no effect of either on regressions, and the interaction of the two factors was marginal by items but did not approach significance in the participants analysis.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, readers made regressive eye movements from this region more frequently when it ended with a comma (12.2% vs. 7.3%; 95% confidence interval of the difference from 1.1% to 8.7%). As noted above, this is consistent with previous findings of increased regressions before a clause-final comma (Hirotani et al, 2006;Rayner et al, 2000). There was no effect of either on regressions, and the interaction of the two factors was marginal by items but did not approach significance in the participants analysis.…”
Section: Resultssupporting
confidence: 91%
“…The same studies that have found increased regressive eye movements before a clause-final comma (Hirotani et al, 2006;Rayner et al, 2000) have also found that the saccade that crosses a clause boundary tends to be longer when a comma is present at the boundary than when a comma is absent. As a result, the eyes tend to land further into the next region in the presence of a comma.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The authors suggest that these differences might simply be due to the complex semantics of counterfactuals, since the end of a sentence is thought to hold a special status for 'wrap-up' processing (e.g. Just & Carpenter, 1980;Rayner, Kambe, & Duffy, 2000).…”
Section: Discussionmentioning
confidence: 99%